Las inscripciones latinas de Totana (Murcia) en la correspondencia y en los Apuntes del presbítero José María Bellón (1816-1894) - González Fernández, Rafael; Martínez Cavero, Pedro (Documenta & Instrumenta - Documenta et Instrumenta, 2010)
In this work, we deal with the unknown figure of a local scholar of the nineteenth century, Jose Maria Bellón Molino, a priest, native of Totana (Murcia), who through his epistolary relationship with Aureli-ano Fernandez-Guerra y Orbe (from March 1864 and March 1865) sent to Emil Hübner information (with photos) on inscriptions that were kept in Totana and would be published five years later in the epigraphic corpus edited in Berlin (CIL II 3531, 3533 and 3534).
Keywords: CIL; Bellon; Fernandez-Guerra; Totana; Inscriptions